Effects of thermal transformation on graphene-like lamellar porous carbon and surface-contributed capacitance. (December 2021) - Sun, Yuzhen; Liu, Yu; Han, Yuting; Li, Ziyi; Ning, Guoqing; Xing, Rong; Ma, Xinlong
Abstract: Considering that graphene is one layer of graphite, which has some amazing properties. It is expected that graphene-like lamellar porous carbons (PCs) can be directly formed by a simple thermal treatment, which has not been realized. Here, we present a simple and scalable synthesis of graphene-like lamellar PCs via thermal transformation of asphalt at the temperature of 700–1600 °C. The electronic properties of PCs under different temperatures are calculated by CASTEP simulations based on density functional theory (DFT). The results show reduction in band gap for PC700, PC900, PC1200 and PC1600, which are 1.781, 1.624, 1.486 and 1.33 eV, respectively. Moreover, the values of electron density difference for PC700, PC900, PC1200 and PC1600 are 4.004 × 10 −2, 4.849 × 10 −2, 3.077 × 10 −2, 8.368 × 10 −2 Bohr −3, respectively. These results imply that the PC1200 possesses the higher conductivity, smallest electron density difference and more even electron distribution. Interesting enough, the experimental results are in good agreement with this theoretical prediction. That is to say, the 1200 °C thermally-treated PC (PC1200) exhibits higher specific capacitance of 162 F g −1 at 1 A g −1 and excellent cycling stability (remain 94% after 10, 000 cycles) in aqueous electrolyte and Li-ion capacitors (LICs). As a result, the PC1200 materials are promising for large-scale and practical applications in LICs. Graphical Abstract: ga1